2008
DOI: 10.22621/cfn.v122i1.538
|View full text |Cite
|
Sign up to set email alerts
|

Eye Colour, Aging, and Decoy Trap Bias in Lesser Scaup, <em>Aythya affinis</em>

Abstract: Researchers routinely assume that samples of trapped or captured animals are representative of the overall population, though these assumptions are not always evaluated. We used decoy-trapped Lesser Scaup (Aythya affinis) to assess the reliability of classifying females as yearlings or adults from a distance, based on documented age-related eye-colour changes, and also to evaluate the presence of sex, condition and age biases in decoy trapping. We compared eye colour of trapped females to photographs of known-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…For scoters, non‐egg‐producing females were on average lighter than egg‐producing females and tended to have bursa present (S. M. Slattery, unpublished data), indicating that they were younger or reproductively inexperienced birds (Mather and Esler ). For scaup, eye color (Trauger ) indicated that our decoy‐trapped females were on average younger than nest‐trapped birds (S. M. Slattery, unpublished data), consistent with previous findings of decoy trap bias toward younger or poorer quality individuals (Weatherhead and Greenwood , Fast et al ). In addition, we detected evidence of subsequent nesting in only a few decoy‐trapped scaup in the year of trapping (S. M. Slattery, unpublished data), much like Martin et al ().…”
Section: Discussionsupporting
confidence: 88%
“…For scoters, non‐egg‐producing females were on average lighter than egg‐producing females and tended to have bursa present (S. M. Slattery, unpublished data), indicating that they were younger or reproductively inexperienced birds (Mather and Esler ). For scaup, eye color (Trauger ) indicated that our decoy‐trapped females were on average younger than nest‐trapped birds (S. M. Slattery, unpublished data), consistent with previous findings of decoy trap bias toward younger or poorer quality individuals (Weatherhead and Greenwood , Fast et al ). In addition, we detected evidence of subsequent nesting in only a few decoy‐trapped scaup in the year of trapping (S. M. Slattery, unpublished data), much like Martin et al ().…”
Section: Discussionsupporting
confidence: 88%